2017
DOI: 10.22499/3.6604.003
|View full text |Cite
|
Sign up to set email alerts
|

Extreme monthly rainfall over Australia in a changing climate

Abstract: Motivated by the important impacts of extreme rainfall, this study extends the CSIRO and BoM (2015) analyses and projections of 20-year means and daily extremes to rainfall on the monthly timescale. Frequency distributions for monthly rainfall rates simulated by 40 CMIP5 models for the 1986-2005 period are compared with those from the AWAP 0.25° gridded observational data. Distributions spatially-averaged over Australian regions provide a signature of seasonal rainfall. Composites of months in the top and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The analysis of extreme monthly precipitation previously applied to CMIP5 by Watterson et al . (2016) has been applied here to two 20‐year periods (starting with P1) of data from each of our CMIP6 simulations. At each model grid point, the top decile of monthly rain rate values in each of the four seasons is determined in each period.…”
Section: Analysis Of Atmospheric Moisturementioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of extreme monthly precipitation previously applied to CMIP5 by Watterson et al . (2016) has been applied here to two 20‐year periods (starting with P1) of data from each of our CMIP6 simulations. At each model grid point, the top decile of monthly rain rate values in each of the four seasons is determined in each period.…”
Section: Analysis Of Atmospheric Moisturementioning
confidence: 99%
“…Correlations for pr and prw are also moderate, with both being broadly larger at warmer latitudes. The high r between the mean (pr) and high monthly (pr‐H) rain fields reflects a similar local ratio between the two statistics for most regions (Watterson et al ., 2016). The link between pr and conv is enhanced with the H composite.…”
Section: Relationships Between Rainfall and Moisture Variablesmentioning
confidence: 99%
“…They also found that persistence is enhanced following wetter months, thus, if monthly rainfall is projected to increase towards the end of the century, perhaps persistence will also increase. While extreme daily rainfall is projected to increase over Australia by the end of the century (CSIRO and Bureau of Meteorology 2015), with the wettest day of the year becoming wetter, there is not a clear signal that monthly rainfall will also increase (Watterson et al 2016). However, across southern Australia, where winter and spring mean rainfall are projected to decline, the reduction in the value of the top decile is less than for the median or lowest decile (Watterson et al 2016) indicating that there might be a relative increase in extreme monthly rainfall compared to a reducing mean.…”
Section: Introductionmentioning
confidence: 99%
“…While extreme daily rainfall is projected to increase over Australia by the end of the century (CSIRO and Bureau of Meteorology 2015), with the wettest day of the year becoming wetter, there is not a clear signal that monthly rainfall will also increase (Watterson et al 2016). However, across southern Australia, where winter and spring mean rainfall are projected to decline, the reduction in the value of the top decile is less than for the median or lowest decile (Watterson et al 2016) indicating that there might be a relative increase in extreme monthly rainfall compared to a reducing mean. The persistence of temperature anomalies is likely to be tied to both the rainfall persistence and the progression of evapotranspiration and soil moisture anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…While it represents a considerable challenge to provide robust results that are clearly communicated for stakeholders to use as part of their decision-making processes, these annual reports are increasingly showing their potential to help meet such growing needs. Extreme rainfall on a range of time scales is expected to become more extreme in a warmer world (e.g., Allan and Soden 2008;Held and Soden 2006) particularly at subdaily time scales (Westra et al 2014), but also on daily (CSIRO and Bureau of Meteorology 2015) and monthly time scales (Watterson et al 2016). Observed trends toward higher intensity rainfall have been found in many regions around the globe (Westra et al 2013).…”
mentioning
confidence: 99%